Red dust rising : the story of Ray Fryer of Urapunga - Houldsworth, Marion (Moorooka, Qld. : Boolarong Press, 2011)
This is the inspiring story of a northern cattleman who built up the Urapunga cattle station from nothing. From the 1950s to the 1990s, he lived rough and worked hard. He worked closely with the tribal Aborigines, made Urapunga a dry station, coped with the many crocodiles in the Roper River, fought against cattle diseases, hunted buffalo, built himself a homestead and survived. Ray Fryer says of himself, "I always admired those old-time pioneers, the Duracks and the Buchanans. I wanted to do something like them; something worthwhile."
Previously published: Rockhampton, Qld. : Central Queensland University Press, 2004.
Includes bibliographical references and index.
Also available in an electronic version via the Internet.
Keywords: Fryer, Ray; Cattle breeders -- Northern Territory -- Roper River Region -- Biography; Ranch life -- Northern Territory -- Roper River Region -- Biography; Ritharrngu / Ridharrngu people (N104) (NT SD53-07); Ngalakan people (N77) (NT SE53-02); Enterprises - Pastoral industry; History - Biographies - Non-Indigenous - Autobiographies; Land rights - Pastoral industry; Roper River Region (N.T.) -- Biography; Urapunga (NT Top End Roper SD53-10); Roper River (NT Top End SD53-09, SD53-10, SD53-11); Australian